Tendencies in Foreign Tourism to the Lublin Voivodship During the Years 2001-2008 - Bergier, Józef; Soroka, Andrzej (Regional Barometer. Analyses & Prognoses, 2010)
The article discusses tendencies relating to foreign tourism in the area of the Lubelskie district in 2001-2008, including the number of border crossings by foreigners, and the number of tourists. In the case of tourists’ arrival, the following criteria were taken into consideration: the visits made for tourist reasons only, the number of accommodations for the night, the length of stay, and the carried expenses. A further analysis concentrates on the reasons for the decrease in arrivals to the Lubelszczyzna as well as the positive phenomena connected with the redefining of reasons for coming to the Lubelskie district. Moreover, the paper mentions a chance of foreign guests being interested in the Lubelszczyzna thanks to the creation of air transportation infrastructure in Świdnik near Lublin.